Hypoxia and Human Diseases 2017
DOI: 10.5772/65339
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoxia-Reoxygenation Injury Model

Abstract: Hypoxia-reoxygenation injury is a commonly used in vitro model of ischemia, which is useful to study the recovery processes following the hypoxic period. Hypoxia can be rapidly induced in vitro by replacing the culture atmosphere with hypoxic or anoxic gas mixture. Cellular injury mostly occurs as a result of energetic failure in this model: the lack of oxygen blocks the mitochondrial respiration and anaerobic metabolism becomes the major source of high-energy molecules in the cells. In the absence of glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
(137 reference statements)
1
2
0
Order By: Relevance
“…The acquired results indicated a 17% reduction in the metabolic activity of untreated cells following the cycle of hypoxia and reoxygenation compared to healthy cells (normoxia control) (Figure 1). This result validates our hypoxia and reoxygenation model, as it was established that cells undergo shifts in metabolic requirements during hypoxia, and the effort to restore them during reoxygenation can lead to cellular component damage and impact cell metabolic activity [15].…”
Section: Sars-cov-2 Reduces Primary Cardiomyocyte Metabolic Activitysupporting
confidence: 86%
“…The acquired results indicated a 17% reduction in the metabolic activity of untreated cells following the cycle of hypoxia and reoxygenation compared to healthy cells (normoxia control) (Figure 1). This result validates our hypoxia and reoxygenation model, as it was established that cells undergo shifts in metabolic requirements during hypoxia, and the effort to restore them during reoxygenation can lead to cellular component damage and impact cell metabolic activity [15].…”
Section: Sars-cov-2 Reduces Primary Cardiomyocyte Metabolic Activitysupporting
confidence: 86%
“…Previous studies have demonstrated that the intracellular effects and cellular injury caused by hypoxia-reoxygenation (H/R) in vitro are similar to the responses induced by ischemia-reperfusion in vivo (Samaja and Milano, 2015;Gerõ, 2017). Under hypoxia, cells undergo energy depletion and transform from aerobic mitochondrial respiration into anaerobic metabolism, which induces intracellular acidosis via increasing intracellular concentrations of lactate and protons, and results in disequilibrium of the cytoplasmic concentrations of sodium and calcium ions (Gourdin and Dubois, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxia, cells undergo energy depletion and transform from aerobic mitochondrial respiration into anaerobic metabolism, which induces intracellular acidosis via increasing intracellular concentrations of lactate and protons, and results in disequilibrium of the cytoplasmic concentrations of sodium and calcium ions (Gourdin and Dubois, 2017). Upon reperfusion or reoxygenation after a period of hypoxia, there will be intramitochondrial calcium overload and accumulation of reactive oxygen species (ROS) due to a sudden increase of intramitochondrial oxygen molecules and dramatic decrease of intracellular protons, and hence leading to opening of the mitochondrial permeability transition pore, which then induces cell apoptosis (Kalogeris et al, 2012;Gerõ, 2017). It has been reported that ischemia-reperfusion is a common hemorheological situation associated with solid organ transplantation, including lung transplantation (Fiser et al, 2002;de Perrot et al, 2003;Cicco et al, 2005;Kosieradzki and Rowinski, 2008;Lobo et al, 2014;Chen and Date, 2015;Laubach and Sharma, 2016), and that interruption of bronchial artery circulation during lung transplantation is highly associated with airway ischemia/hypoxia, pulmonary fibrosis, bronchiolitis obliterans syndrome, susceptibility to chronic rejection, and low long-term survival (Nicolls and Zamora, 2010;Wilkes, 2010;Tong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%